(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
A systematic review was conducted on the production and publication of research papers concerning the study of Tax Reforms, Income Tax, Public Budget, during the period between 2017 and 2022 under the PRISMA approach (Preferred Reporting Items for Systematic reviews and Meta-Analyses). The objective of the analysis proposed in this work was to know the main characteristics of the publications registered in the Scopus and Wos databases and their scope in the study of the proposed variables, achieving the identification of 67 publications in total. In addition to this first identification, it was possible to refine the results through the keywords entered in the search button of both platforms, which were TAX REFORMS, INCOME TAX, PUBLIC BUDGET, reaching a total of 16 documents, excluding duplicates and those that did not meet the analysis criteria. From this analysis it is expected to know the contributions of the scientific community to the study of the management of taxes such as the Value Added Tax (VAT) in the elderly community. It is expected to find a relationship between the reforms carried out in taxation, specifically in the applied personal income tax, and the annual allocation of the public expenditure budget. In this case, to determine the contribution of the scientific community to the study of the impacts generated in the allocation of the budget for the elderly.